THE ROLE IDENTITY AS THE BASIC CONSTRUCT OF THE SPECIALIST‘S SOCIAL COMPETENCE - Fruktova, Y. S. (Continuing Professional Education: Theory and Practice, 2019)
In modern terms for university graduates especially important to be understanding the social significance of their profession and therefore understanding its place in the system of social relations, and the ability to critical evaluation of his life and professional experience, a conscious choice of ways and methods to improve personal and professional qualities. Due to the pressing problems of socialization specialist in modern scientific literature in higher education (government, industry, universities) much attention is paid to the key, socalled social competencies. The article deals with theoretical aspects of determining the content and structure of the social competence of specialists, in particular its social role component. Indicated by current approaches to classification of roles, their stage of development, role expectations and demands of society stereotypes, assumptions role identity. Today, social scientists subject is considered as a person who not only learns the social demands, but also selfproduces important social needs for himself and directs efforts to implement them, guided in their behavior prevailing value orientations and ideals, reveals a certain limit, not be antisocial, autonomy, ie isolation, isolation from society. In achieving social competence should be interested as the personality and society.